Propuesta de diseño de la línea de producción de un nuevo snack en una empresa de alimentos - Yandún Rodríguez, Daniel Martín (2018)
This article focuses on developing the proposal for the design of a production line for a new snack for an SME type food company, with operations mainly in Ecuador and the United States, whose objective is to bring health and well being through its own Ecuadorian food based products. The main objective is to present a feasible production line to the reality of the company and the country, but at the same time demonstrate that Ecuador can also be at the forefront in terms of innovation and quality of food products. The fulfillment of this objective implied the use of lean manufacturing tools such as: process diagramming, identification of seedlings, 5 S, just in time, standardization of work, distribution and location of plant, among others. After conducting two simulations through the Flexsim design software, and a financial feasibility study. It was evidenced that the first proposal could eliminate on average 31 percent the waste of the current process. The second proposal demonstrates the profitability of creating its own plant with a more effective line than the previous one, establishing as equilibrium point only 859 units above the estimated annual sale, giving a relatively short waiting time to start making profits. A layout was made for the last proposal based on the norms and ordinances in force within the Metropolitan District of Quito, ensuring a distribution of spaces and machinery suitable to consolidate lean manufacturing with a fully functional U working cell that allows the expansion of the operations of the plant by 34 percent if required and ideal for batch production to satisfy a production oriented to a PULL strategy.